PENGARUH PENDIDIKAN GIZI TERHADAP PENINGKATAN PENGETAHUAN GIZI IBU HAMIL ANEMIA DI PUSKESMAS SIDOMULYO RAWAT INAP KOTA PEKANBARU - besti verawati; Nopri Yanto; Annisa Wulandarri (Jurnal Doppler, 2021)
Knowledge of nutrition and iron deficiency are factors that cause anemia in pregnant women. The prevalence of anemia in pregnant women is always increasing every year. Some efforts that can be made to increase hemoglobin levels are providing nutrition education. The aim of the study was to analyze the effect of nutrition education n the increase in hemoglobin levels of anemic pregnant women at Sidomulyo Public Health Center. This type of research is quantitative with a quasi-experimental method with a pretest-posttest design with a control group. The study was conducted June 2020 with a total sample of 30 anemia pregnant women. The data collection techniques used to measure the knowledge of pregnant women were questionnaires, hemoglobin levels using the easytouch. The analysis used was univariate and bivariate with paired sample T-Test and Independent T-Test. The results showed that the average hemoglobin level in the control group before the intervention was 10.2 gr / dl, after the intervention was 10.6 g / dl and the treatment group before the intervention was 10.5 gr / dl and 11.4 gr / dl after the intervention. The results of the paired sample T-test in the control group and the treatment group (0.000), means that there is a significant difference in hemoglobin levels before and after the intervention. The results of the independent sample T-test between groups (0.000), means that there is a significant difference in hemoglobin levels between the control and treatment groups. The conclusion is that there is an effect of nutrition education on hemoglobin levels of anemic pregnant women.